(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2017)
In early ages, especially in Preschool Education, the nomination of mathematical talent by the teacher acquires an important role because the use of standardized tests. However, the objectivity of psychometric tools makes them an increasingly widespread diagnostic element. In this paper, we analyze the items of one of these tests, showing how they correspond to the mathematical tasks suggested by the literature as useful for detecting talent. Our analysis shows that the proposed tasks are not adequate because they focus on procedural aspects, emphasizing their fluidity. We conclude with a series of recommendations so that the teacher of early childhood can use them to detect and to attend the diversity in its classroom.